PENERAPAN INOVASI TEKNIK SAMBUNG SAMPING PADA BUDIDAYA KAKAO DI DESA LATOMA JAYA KECAMATAN LATOMA KABUPATEN KONAWE - Cici Oktavia; Salahuddin Salahuddin; Yoenita Jayadisastera (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2026)
The implementation of side grafting techniques in Latoma Jaya Village is imperative and urgent, as it offers an efficient solution to address the challenges posed by low cocoa productivity, stemming from the dominance of aged plants, substandard seed quality, and limited technological adoption. This approach aims to enhance production, income, and the sustainability of cocoa farming without the need for extensive replanting. The objective of this study is to ascertain the characteristics of innovation and the application of side grafting techniques in cocoa cultivation in Latoma Jaya Village, Konawe Regency. The present study employs a qualitative descriptive approach. The selection of informants was executed through the implementation of a purposive sampling method. The data collection techniques employed in this study included observation, in-depth interviews, and documentation. The objective of the present study was to examine the characteristics of innovation and the application of side grafting techniques in cocoa cultivation. The analysis was executed through a qualitative descriptive approach, encompassing three primary stages: data reduction, data presentation, and conclusion drawing. The findings indicated that the implementation of the innovative side grafting technique in cocoa cultivation in Latoma Jaya Village resulted in significant positive impacts, including enhanced productivity, improved crop quality, and increased farmer well-being. This innovation boasts significant relative advantages, including the capacity to double crop yields in comparison with conventional techniques, while concurrently elevating the selling price of cocoa beans. In terms of compatibility, the side grafting technique is well-suited to the environmental conditions, experience, and cultivation practices of local farmers, facilitating acceptance without the necessity of removing existing plants. Despite its notable complexity, the integration of extensive extension, training, and assistance has been demonstrated to facilitate the successful navigation of technical challenges by farmers. Furthermore, the high trialability and observability of this innovation encourage farmers to gradually adopt it after observing tangible results in their fields.